IMPROVING STUDENTS’ WRITING THROUGH DIARY WRITING - Mega Mulianing Maharani (Proceedings Education and Language International Conference, 2017)
Writing is one of English skills which is categorized as the most difficult skill for second language students. In Indonesia, university students who learn English still find some difficulties in writing. To help the students in facing their problem, the researcher decided to use diary writing as a medium. By using the medium, the writer wanted to know the students’ writing improvement. The researcher used quasi experimental research to find the students’ writing improvement. There were two samples of this research. They were literature students as the control group and education students as the experimental group. The writer applied the technique as the treatment to the experimental group. Before the researcher applied the treatment, the researcher gave a pre-test to the students of literature and education to know their writing ability. After the researcher applied the treatment, the researcher gave a post-test to both groups. The result showed that there was improvement on students’ achievement. It was proven by the value of significant which was 0.005. It was lower than 0.05. Then, it was concluded that diary writing improved the students’ writing. Keywords: students’ writing, diary writing